Is mHealth Disrupting the Status Quo? Evidence from Implementations Highlighting Network vs. Hierarchical Institutional Logics. Issue 1 (5th December 2017) - Asangansi, Ime
Abstract: Health Management Information Systems (HMIS) in developing countries have yet to live up to expectations because of the significant proportion of implementation failures. Mobile health (mHealth) technologies are being adopted increasingly in Ministries of Health (MoHs) to address aspects of HMIS implementation failure, such as the timeliness and ease of data collection from the lowest levels of healthcare. However, networked technologies such as mobile technologies used in mHealth data collection can introduce a network logic into the organization. This network logic, which often favors open, non‐hierarchical modes of communication, must work with the traditional hierarchical bureaucratic logic of the HMIS and the MoH in which they become embedded. This paper conceptualizes the interaction between these two logics. It draws on succinct, empirical vignettes from two action‐research projects involving the use of mHealth technology to improve data collection for the HMIS in Nigeria. Based on these findings and an institutional logics lens, this paper argues that the interaction between these logics potentially leads to a conflict where the logic embedded in networked technologies (such as mHealth) disrupts and challenges the existing hierarchical logic in the bureaucracy (such as in the MoH). It threatens not only to unsettle existing practices and norms in the organization, but also to restructure (flatten) the organization, due to resistance, loss, or changes in some pre‐existing roles. Practitioners and implementation researchers need to be sensitive to potential hierarchical and network‐centric forces that are involved in implementing mHealth in traditional hierarchical settings, particularly with regards to the unintended side effects that may arise in the process.